An Atherogenic Index of Plasma in Type 2 Diabetes Mellitus with and without Coronary Artery Disease - Oktarina, Nur Hasni; Kurniawan, Liong Boy; Nurahmi, Nurahmi (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Chronic hyperglycemia causes an increase in glycosylation products that induce inflammation and injury to the arterial wall, which will cause changes in the vascular tissue resulting in atherosclerosis. The Atherogenic Index of Plasma (AIP) has been suggested as a biomarker for atherosclerosis and has demonstrated a strong correlation with other atherosclerosis indices, including small dense LDL and LDL cholesterol. This study aimed to determine the AIP in Type 2 Diabetes Mellitus (T2DM) patients with and without Coronary Artery Disease (CAD) complications. A retrospective cross-sectional study using medical record data of 73 T2DM patients without CAD complications and 73 T2DM patients with CAD complications at Dr. Wahidin Sudirohusodo General Hospital was carried out from January to December 2022. The diagnosis of T2DM and CAD was based on the clinician's diagnosis. An atherogenic index of plasma was calculated as log (triglyceride/HDL cholesterol). Samples were analyzed using SPSS version 25, using the Kolmogorov-Smirnov statistical test to assess data normality, Mann-Whitney test, the Receiver Operating Characteristics (ROC) curve to assess Area Under Curve (AUC), and a determination of cut-off values. Statistical test results with p-values <0.05 were reported as significant. Atherogenic index of plasma values was significantly higher in T2DM with CAD complications than without CAD complications (0.51±0.25 vs. 0.30±0.11, p<0.001). The ROC curve analysis showed an optimal cut-off value of 0.36 to predict T2DM with CAD with 71% sensitivity, 62% specificity, and 66% accuracy. There was a significant association between high AIP values and CAD complications in T2DM. An atherogenic index of plasma value can be used to predict T2DM with CAD.